Defect‐Free Metal–Organic Framework Membrane for Precise Ion/Solvent Separation toward Highly Stable Magnesium Metal Anode - Zhang, Yijie; Li, Jiang; Zhao, Wanyu; Dou, Huanglin; Zhao, Xiaoli; Liu, Yuan; Zhang, Bowen; Yang, Xiaowei (Advanced materials (Weinheim), 2022)
Metallic magnesium batteries are promising candidates beyond lithium‐ion batteries; however, a passive interfacial layer because of the electro‐reduction of solvents on Mg surfaces usually leads to ultrahigh overpotential for the reversible Mg chemistry. Inspired by the excellent separation effect of permselective metal–organic framework (MOF) at angstrom scale, a large‐area and defect‐free MOF membrane directly on Mg surfaces is here constructed. In this process, the electrochemical deprotonation of ligand can be facilitated to afford the self‐correcting of intercrystalline voids until a seamless membrane formed, which can eliminate nonselective intercrystalline diffusion of electrolyte and realize selective Mg2+ transport but precisely separate the solvent molecules from the MOF channels. Compared with the continuous solvent reduction on bare Mg anode, the as‐constructed MOF membrane is demonstrated to significantly stabilize the Mg electrode via suppressing the permeation of solvents, hence contributing to a low‐overpotential plating/stripping in conventional electrolytes. The concept is demonstrated that membrane separation can serve as solid‐electrolyte interphase, which would be widely applicable to other energy‐storage systems. An artificial solid‐electrolyte interphase enabled by an intact metal–organic framework (MOF) membrane is constructed directly on Mg foils. Through precious solvent molecule/Mg ion sieve owing to the angstrom‐sized aperture window, the MOF membrane suppresses the solvent reduction and enables a low migration barrier for Mg2+ transportation within this MOF‐based solid‐electrolyte interphase.